Modified atmosphere packaging and post-packaging irradiation of Rumex induratus leaves: a comparative study of postharvest quality changes - Pinela, José (2016)
The effects of conventional and inert-gas enriched atmospheres, as well as those caused by different γ-irradiation doses, on buckler sorrel (Rumex induratus) leaves quality were evaluated and compared after 12 days of storage at 4 °C. The green colour of the abaxial surface of the leaves was relatively stable, as well as the carbohydrates content and the calorific value. The storage time decreased the amounts of fructose, glucose, trehalose, α-tocopherol, and β-tocopherol and increased the levels of total organic acids and δ-tocopherol. The total tocopherols content was higher in air-packaged non-irradiated leaves, antioxidant compounds that may have contributed to the preservation of polyunsaturated fatty acids (PUFA). Some antioxidant properties were also favoured during storage. It was found that the overall postharvest quality of buckler sorrel leaves is better maintained with the argon-enriched atmospheres, while the 6 kGy dose was a suitable option to preserve PUF+A during cold storage. This study highlights the suitability of the applied postharvest treatments and the interest to include buckler sorrel leaves in contemporary diets.